2019
DOI: 10.29245/2572.942x/2019/1.1261
|View full text |Cite
|
Sign up to set email alerts
|

Tri-Allelic Human Leukocyte Antigen (HLA) Protection Against Dementia

Abstract: Human Leukocyte Antigen (HLA) Class II DRB1*13:02 has recently been found to protect against dementia in Continental Western Europe. Here we extend those findings by evaluating the association between the population frequency of two additional Class II HLA alleles -DRB1*01:01 and DRB1*15:01 -alone and in combination with DRB1*13:02, on dementia prevalence in Continental Western Europe. Results indicated that the prevalence of dementia in 14 Continental Western European (CWE) countries significantly decreased e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 25 publications
(39 reference statements)
2
26
0
Order By: Relevance
“…Using a publicly available repository 21 containing HLA data pooled from histocompatibility laboratories and published studies, coupled with dementia prevalence obtained from the Global Burden of Disease studies 1 we have examined associations between HLA and dementia prevalence in 14 countries in Continental Western Europe where dementia prevalence is among the highest in the world. We demonstrated that three specific Class II HLA DRB1 alleles -DRB1*01:01, DRB1*13:02, and DRB1*15:01 -are highly protective against dementia, even after accounting for apolipoprotein E4 17 . Moreover, the combined population frequency of the three alleles accounted for 67% of the variance in dementia prevalence and 48% of the change in dementia prevalence in those countries over the last 25 years.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Using a publicly available repository 21 containing HLA data pooled from histocompatibility laboratories and published studies, coupled with dementia prevalence obtained from the Global Burden of Disease studies 1 we have examined associations between HLA and dementia prevalence in 14 countries in Continental Western Europe where dementia prevalence is among the highest in the world. We demonstrated that three specific Class II HLA DRB1 alleles -DRB1*01:01, DRB1*13:02, and DRB1*15:01 -are highly protective against dementia, even after accounting for apolipoprotein E4 17 . Moreover, the combined population frequency of the three alleles accounted for 67% of the variance in dementia prevalence and 48% of the change in dementia prevalence in those countries over the last 25 years.…”
Section: Introductionmentioning
confidence: 86%
“…As in our previous studies 16,17 we focused on the following 14 CWE countries: Austria, Belgium, Denmark, Finland, France, Germany, Greece, Italy, Netherlands, Portugal, Norway, Spain, Sweden, and Switzerland.…”
Section: Cwe Countriesmentioning
confidence: 99%
See 3 more Smart Citations